Failed Implementation of Western Democracy in the Middle East - Fika Nurislamia; Surwandono Surwandono (Prodi Hubungan Internasional Program Magister Univ. Muhammadiyah Yogyakarta, 2023)
This article discusses how Peace Democratic Theory works as a foreign policy of the United States inspreading democracy around the world, especially in Islamic countries in the Middle East, and howthe Islamic left criticizes the democratization process due to this foreign policy. Peace DemocraticTheory ushers in Islamic Leftist Thought in assessing how the democratization process works out ofconformity with Islamic Shari'a and the resulting chaos and prolonged conflict. The author brings acase study of the Iraq conflict due to the democratization process's failure in this article. Using adescriptive qualitative approach, the author concluded that Peace Democratic Theory gave birth todemocracy that established oligarchic politics. This article contributes information for various partieson the reasons for thinking about criticism between Islam and Peace Democratic Theory. In addition,this article is information material for multiple parties related to strategy in the conflict between Islamand Peace Democratic Theory.